Simple equations for predicting the rotational ductility of fiber-reinforced-polymer strengthened reinforced concrete joints. (April 2020) - Abu Tahnat, Yazan B.; Samaaneh, Mohammad A.; Dwaikat, Mahmud M.S.; Halahla, Abdulsamee M.
Abstract: Achieving a certain limit of rotational ductility in retrofitted reinforced concrete (R.C) joints is very important in the design of earthquake-resistant structures. Strengthening of R.C joints using wraps of fiber-reinforced polymers (FRP) is a common attractive technique and has an effect on the ductility of such joints. This study focuses on developing simple conceptual equations to predict the ductility of exterior reinforced concrete (R.C) beam-column joints as a function of the applied FRP. The equations are derived based on statistical regression through parametric study using results from a high-fidelity finite element model created using ABAQUS. The validated model includes material and geometric nonlinearities, in addition to the use of realistic nonlinear contact behavior between FRP and concrete. The proposed simple equations can be used as an initial conceptual design step for checking the adequacy of R.C beam-column joints in seismic design of R.C buildings. The proposed equations consider FRP, relative column-to-beam inertia, and transverse reinforcement in the beam and joint as the main parameter. This study defines the types of failure based on the ductility, and it develops the equations for ductile and brittle failures for both CFRP-strengthened joints and non-strengthened joints. This research confirms quantitatively the effectiveness of using CFRP to increase the ductility in most cases of the R.C beam-column joints. However, contribution of the CFRP is limited for some cases.